The Role of Digital Technologies in Modern Education (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The article analyzes the advantages and disadvantages of electronic education, shows the forms of digitalization that require a comprehensive approach from the education system, which would set new goals, change the structure and content of the educational process. The author formulated a hypothesis about the need for their scientifically based implementation in the work of higher and vocational education organizations. The article is intended for employees of the higher and vocational education system.